Peningkatan Kompetensi Pustakawan Melalui Penerapan Otomasi Perpustakaan di Perpustakaan SMKN 3 Bandung - Hasanah, Nur Alif; Indah, Rosiana Nurwa; Achmad Syam, Rifqy Zaeni (Universitas Negeri Padang, 2021)
This study aims to determine the competence of librarians, which will certainly have a major influence on the development of libraries, supported by a slim-based information technology system, to what extent librarians' competence through the application of automation using window theory contains three indicators, namely: knowledge, skills and attitudes. This research uses descriptive qualitative method with interview techniques. Based on the results, the implementation of this automation system can make it easier for librarians to complete their tasks. The school librarian participates in various activities such as practices that are followed during lectures, training and other seminars organized by the government for those who do not have a library educational background. This can increase the librarian's competence after carrying out these activities. At the time of implementing this automation system, librarians experience several problems, such as unstable internet networks, inadequate computers, and computers that often interfere with data loss, therefore librarians still apply manual systems.